CONCEPTS OF BUSINESS BY ISLAMIC VIEWS - H. Y. Ahmad Mujahideen; M. Z. Razali; M. H. Norhidyah (Journal of Islamic, Social, Economics and Development, 2019)
In life, humans need to rule out to ensure the harmony of life. Without regulation, human life becomes unmanageable and disruptive. Islam is a perfect religion that has set certain rules among the rules related to business activities. This article is a fully qualitative study article. This article aims to explain the definition of business and further debate on the concepts business as outlined by Islam. The findings of this article are to know the meaning of the business and to break down the concepts business according to Islamic views aimed at providing the right guidelines for Muslims in carrying out business activities and thus exposing the excellence and perfection of Islam as a universal religion that is always in keeping and fulfilling the needs and demands of human life especially in business.